Perbandingan Morfologi Stroberi (Fragaria SPP) Di La Fressa Dan Bukit Strawberry Lembang Untuk Klasifikasi Varietas - Nathania Rahadatul ‘Aisy; Yulia Agustin; Ateng Supriatna (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Indonesia is a tropical country, yet its highlands can produce one of the economically valuable types of subtropical fruit, one of which is the strawberry. Strawberry plants are highly profitable fruit plants and come in many variations. Their small and attractive shape, along with their sweet and fresh taste, make these fruits appealing. In Indonesia, strawberry farmers perform interspecies crossings, leading to the growth of many varieties. Indonesia, particularly West Java, is one of the environments suitable for strawberry growth, with Lembang in West Bandung Regency being a prime example. Therefore, this research aims to compare plant cultivars by combining the morphological characteristics of three varieties obtained from two locations, La Fressa and Bukit Strawberry, Lembang. The method used for identifying the diversity of strawberry plant characteristics is the FGD (Focus Group Discussion) method, which is then described specifically according to the morphology of the obtained plant varieties.